PENILAIAN AUTENTIK DALAM PEMBELAJARAN MATEMATIKA - Laelasari Laelasari (LP2M Universitas Sarjanawiyata Tamansiswa, 2017)
Authentic assessment or direct assessment is important in the learning process activities that have been implemented. The design of an authentic assessment instrument can know the competencies achieved at the time of the KBM activities. Authentic assessment is a form of assessment that can describe actual learning outcomes, can use various techniques, including through project appraisal, or student activities, portfolio use, journal, demonstration, written reports, checklists and observation instructions. Through an authentic assessment of a teacher can know the level of success and achievement of students in receiving learning material in real or factual. The authentic assessment gives students the opportunity to show what they have mastered and learned. The seven basic skills that need to be assessed on authentic assessment include, visual-spatial, bodily-kinesthetic, musical-rhythmical, interpersonal, logical mathematical, verbal, and linguistic. The development of authentic assessment includes four ways, 1). standard setting; 2). authentic task determination; 3). making criteria, and 4). making a rubric.